Long-term mortality following complications after elective surgery: a secondary analysis of pooled data from two prospective cohort studies. (October 2022) - Fowler, Alexander J.; Wan, Yize I.; Prowle, John R.; Chew, Michelle; Campbell, Douglas; Cuthbertson, Brian; Wijeysundera, Duminda N.; Pearse, Rupert; Abbott, Tom
Abstract: Background: Complications after surgery affect survival and quality of life. We aimed to confirm the relationship between postoperative complications and death within 1 yr after surgery. Methods: We conducted a secondary analysis of pooled data from two prospective cohort studies of patients undergoing surgery in five high-income countries between 2012 and 2014. Exposure was any complication within 30 days after surgery. Primary outcome was death within 1 yr after surgery, ascertained by direct follow-up or linkage to national registers. We adjusted for clinically important covariates using a mixed-effect multivariable Cox proportional hazards regression model. We conducted a planned subgroup analysis by type of complication. Data are presented as mean with standard deviation (sd ), n (%), and adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs). Results: The pooled cohort included 10 132 patients. After excluding 399 (3.9%) patients with missing data or incomplete follow-up, 9733 patients were analysed. The mean age was 59 [sd 16.8] yr, and 5362 (55.1%) were female. Of 9733 patients, 1841 (18.9%) had complications within 30 days after surgery, and 319 (3.3%) died within 1 yr after surgery. Of 1841 patients with complications, 138 (7.5%) died within 1 yr after surgery compared with 181 (2.3%) of 7892 patients without complications (aHR 1.94 [95% CI: 1.53–2.46]). Respiratory failure was associated with the highest risk of death, resulting in six deaths amongst 28 patients (21.4%). Conclusions: Postoperative complications are associated with increased mortality at 1 yr. Further research is needed to identify patients at risk of complications and to reduce mortality.